Addressing Colon Cancer Screening Disparities among Overweight and Obese Women - Sara M. Kennedy (University of North Florida, 2011)
Colon cancer is the third most common cancer in women and 60% ofdeaths from colon cancer could be prevented ifpersons 50 and older were screened regularly. Whereas physician recommendation has been identified as critical to increasing colon cancer screening, this factor may be insufficient for increasing colon cancer screening adherence among overweight and obese women. Despite having more physician visits, this population tends to receive fewer preventative services. Women who delay routine cancer screening have the highest rates ofdieting. An intervention utilizing the recommendation for screening from a weight loss advisor at an organization like may prove to be effective. This is an opportunity for health educators to direct weight loss organizations to implement new interventions aimed at increasing colon cancer screening. Cancer screening information disseminated through such organizations has focused almost solely on breast cancer. Daniel Goleman's model of leadership may prove to be a valuable guiding framework. An innovative, successful health education program could be created if leaders foster resonance by creating commitment to the overarching vision, achieving consensus through democratic leadership, and ensuring appropriate implementation and necessary motivation through pacesetting.